2021
DOI: 10.1002/ijc.33888
|View full text |Cite
|
Sign up to set email alerts
|

Self‐sampling as the principal modality for population based cervical screening: Five‐year follow‐up of the PaVDaG study

Abstract: Self‐sampling provides a powerful means to engage women in cervical screening. In the original Papillomavirus Dumfries and Galloway study (PaVDaG), we demonstrated cross‐sectional similarity of high‐risk human papillomavirus (Hr‐HPV) testing on self‐taken vaginal vs clinician‐taken samples for the detection of cervical intraepithelial neoplasia 2 or worse (CIN2+). Few data exist on the longitudinal performance of self‐sampling; we present longitudinal outcomes of PaVDaG. Routinely screened women provided a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Self-sampling is now widely accepted as being clinically non-inferior to conventional clinician-taken samples. (22,25,26) Although we found the sensitivity of NS sampling to CIN2+ to be slightly lower than for self-sampling, the confidence intervals overlapped, and no women in the routine screening population were speculum-positive/NS-negative. Given the two collection methods are technically the same, it would be surprising if clinical performance was inferior to self-sampling.…”
Section: Discussionmentioning
confidence: 62%
“…Self-sampling is now widely accepted as being clinically non-inferior to conventional clinician-taken samples. (22,25,26) Although we found the sensitivity of NS sampling to CIN2+ to be slightly lower than for self-sampling, the confidence intervals overlapped, and no women in the routine screening population were speculum-positive/NS-negative. Given the two collection methods are technically the same, it would be surprising if clinical performance was inferior to self-sampling.…”
Section: Discussionmentioning
confidence: 62%
“…There are few reports on the prognostic impact of self-or urine-sampling HPV test results. Stanczuk et al [23] reported longitudinal data on the CIN progression rate with known HPV results 3-5 years after the HPV self-sampling test result. They revealed that the 5-year risk of CIN grade 2 is low in patients with high-risk HPV-negative females performing self-sampling using a polymerase chain reaction-based test [23].…”
Section: Discussionmentioning
confidence: 99%
“…One change idea that we were not able to introduce during our project was self-sampling for those who decline conventional cervical screening, as studies have shown this is acceptable to women,40 and is safe to use within a screening programme 41. A clinical trial of self-sampling commenced in England in 2021 for patients within the NHS CSP 42.…”
Section: Discussionmentioning
confidence: 99%